Impact of SCBA size and fatigue from different firefighting work cycles on firefighter gait. Issue 9 (2nd September 2018) - Kesler, Richard M.; Bradley, Faith F.; Deetjen, Grace S.; Angelini, Michael J.; Petrucci, Matthew N.; Rosengren, Karl S.; Horn, Gavin P.; Hsiao-Wecksler, Elizabeth T.
Abstract: Risk of slips, trips and falls in firefighters maybe influenced by the firefighter's equipment and duration of firefighting. This study examined the impact of a four self-contained breathing apparatus (SCBA) three SCBA of increasing size and a prototype design and three work cycles one bout (1B), two bouts with a five - minute break (2B) and two bouts back - to - back (BB) on gait in 30 firefighters. Five gait parameters (double support time, single support time, stride length, step width and stride velocity) were examined pre- and post-firefighting activity. The two largest SCBA resulted in longer double support times relative to the smallest SCBA. Multiple bouts of firefighting activity resulted in increased single and double support time and decreased stride length, step width and stride velocity. These results suggest that with larger SCBA or longer durations of activity, firefighters may adopt more conservative gait patterns to minimise fall risk. Practitioner Summary: The effects of four self-contained breathing apparatus (SCBA) and three work cycles on five gait parameters were examined pre- and post-firefighting activity. Both SCBA size and work cycle affected gait. The two largest SCBA resulted in longer double support times. Multiple bouts of activity resulted in more conservative gait patterns.